2019
DOI: 10.3390/molecules24224173
|View full text |Cite
|
Sign up to set email alerts
|

The Analogs of Temporin-GHa Exhibit a Broader Spectrum of Antimicrobial Activity and a Stronger Antibiofilm Potential against Staphylococcus aureus

Abstract: The abuse of antibiotics has led to the emergence of multidrug-resistant bacteria, which is becoming a serious worldwide problem people have to face. In our previous study, temporin-GHa (GHa) cloned from Hylarana guentheri showed antimicrobial activity against Gram-positive bacteria. In order to improve its therapeutic potential, we used a template-based and a database-assisted design to obtain three derived peptides by replacing the histidine at both ends of GHa with lysine, which exhibited faster and stronge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 43 publications
(53 reference statements)
0
25
0
Order By: Relevance
“…Therefore, the search for alternative compounds to counteract S. aureus infections is in highly demand [ 39 , 40 ]. Temporins are a family of frog-skin AMPs whose various isoforms have already shown activity against Gram-positive bacteria [ 23 , 41 , 42 ]. For instance, TA has a MIC ranging from 4 to 16 µg/mL towards human methicillin-resistant S. aureus (MRSA) clinical isolates [ 18 ]; TB and different synthetic analogs inhibit the growth of various S. aureus strains alone or in combination with TA [ 22 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the search for alternative compounds to counteract S. aureus infections is in highly demand [ 39 , 40 ]. Temporins are a family of frog-skin AMPs whose various isoforms have already shown activity against Gram-positive bacteria [ 23 , 41 , 42 ]. For instance, TA has a MIC ranging from 4 to 16 µg/mL towards human methicillin-resistant S. aureus (MRSA) clinical isolates [ 18 ]; TB and different synthetic analogs inhibit the growth of various S. aureus strains alone or in combination with TA [ 22 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…After 24 h of incubation, the minimum peptide concentration able to eradicate biofilm was equal to 64 mg/L. In another recent study conducted by Xie and coworkers, temporin–GHa cloned from Hylarana guenther was found to disrupt 90% of S. aureus biofilm biomass after 24 h of treatment at 100 µM [ 41 ]. A 24 h-long treatment of S. aureus biofilm with two different analogs of TB (at 30 µM) was investigated by Grassi and collaborators with ~1 log (90%) decrease in the number of viable biofilm cells [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Temporins often exhibited potent antimicrobial activity against the growth of Gram-positive bacteria, while the effect on Gram-negative bacteria is weaker [ 26 ]. The antimicrobial killing effect is generally recognized to permeabilize the cell membrane, resulting in the disruption of the structure [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, forming oligomers in some microenvironments, such as lipopolysaccharides (LPS) of Gram-negative bacteria, could escalate the difficulty for temporin to traverse the outer membrane, which weakens the antimicrobial activity on Gram-negative bacteria [ 30 , 33 ]. Therefore, structural modifications and engineering have been continuously implemented for temporins to improve the therapeutic index and efficacy [ 20 , 26 , 30 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…The small temporins are inactive against most bacterial strains ( Simmaco et al, 1996 ), however, truncation of amino acids is widely applied for adjusting peptide physicochemical properties, including membrane affinity ( Feng et al, 2020 ; He et al, 2020 ; Zhu et al, 2020 ). According to previous studies, modification of temporins is always performed via amino acids alteration or terminal sequence addition ( Mangoni et al, 2011 ; Bezzerri et al, 2014 ; Xie et al, 2019 ), the rational truncation of selected amino acid residues is quite rare. In this study, two novel peptide derivatives were intentionally designed to investigate how the truncation of non-charged amino acids affects the bioactivity of small peptides.…”
Section: Resultsmentioning
confidence: 99%